2021
DOI: 10.3390/pr9060988
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Relationship between Wear and Flow Characteristics of a Centrifugal Pump at Different Mass Concentrations

Abstract: In order to study the wear characteristic of a centrifugal pump at different mass concentrations, simulation and experimental research were carried out. The simulation was based on the DPM (discrete phase model) to complete the coupling of particles and the flow field. The experimental research included a performance test and a wear test. Through the comparison of the simulation and experimental research results, the relationship between the particle movement and the wear was analyzed, and the flow field was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It was concluded that the Oka erosion model had the highest accuracy in the ESP, but the computational resources were the most expensive. Jiang et al [33] conducted numerical simulation and experimental research on the wear characteristics of centrifugal pumps with different solid volume fractions. Through the comparison of wear pictures and numerical simulation results, the accuracy of the numerical simulation was verified, and the energy gradient and particle motion were combined to explain the wear characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the Oka erosion model had the highest accuracy in the ESP, but the computational resources were the most expensive. Jiang et al [33] conducted numerical simulation and experimental research on the wear characteristics of centrifugal pumps with different solid volume fractions. Through the comparison of wear pictures and numerical simulation results, the accuracy of the numerical simulation was verified, and the energy gradient and particle motion were combined to explain the wear characteristics.…”
Section: Introductionmentioning
confidence: 99%